The importance of Aboriginal Education Workers for decolonising and promoting culture in primary schools: an analysis of the longitudinal study of Indigenous children (LSIC) - Peacock, H T; Prehn, J (My University, 2019)
Aboriginal Education Workers (AEWs) are utilised by primary and secondary schools to improve components of success for Aboriginal students, liaise with their families and the Aboriginal community and contribute to developing and promoting an Aboriginal pedagogy. Despite the challenging role of decolonising the school environment, the important work undertaken by AEWs can be misunderstood and underappreciated by the Western school system. This paper aims to measure the influence of AEWs on Aboriginal culture within schools using quantitative data from Wave 7 K Cohort of the Longitudinal Study of Indigenous Children (LSIC). Results show that there is a positive impact on Aboriginal culture within schools through having an AEW present all or some of the time. For Aboriginal children to grow up strong, employment of an AEW is important to decolonise the school environment and provide a holistic education.
Australian Journal of Indigenous Education
Keywords: Childhood and child development; Culture and language; Learning, education and training